Termodinâmica da formação de Dímeros de Polimorfos da Carbamazepina : uma análise via propriedades Rovibracionais - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The present study was devoted to the study of the spectroscopic and thermodynamic properties of the polymorph dimer synths of carbamazepine. All electronic structure calculations were performed at the ωB97XD/6-31G(d) level of theory, as implemented in the Gaussian 09 suite of programs. The spectroscopic constants of the system were obtained using theoretical Dunham and discrete variable representation methods, as well as the Rydberg analytical function expanded to the sixth degree. The thermodynamic properties of the polymorphs were obtained with the rovibrational partitioning function of the non-rigid anharmonic rotor.
Thermodynamics of Polymorph Dimer formation of Carbamazepine : an analysis by way of Rovibrational properties
Keywords: Polymorphism; Carbamazepine; Thermodynamic properties; Propriedades espectroscópicas; Polimorfismo; Carbamazepina; Propriedades termodinâmicas; CIENCIAS EXATAS E DA TERRA::QUIMICA